(untitled) (Zien Journal of Social Sciences and Humanities, 2023)
This article analyzes some issues in the development of legal consciousness and legal culture in the process of teaching legal subjects in the public education system, in the process of training managers and pedagogues in the professional development system. Since we believe that one of the urgent issues in our rapidly developing society is the formation of legal consciousness and legal culture, which has its place in the public education system, through the provision of legal knowledge in the process of professional development of leaders and pedagogues, we analyze this issue we decided. In the study, the main source of the law and legal documents was determined